2014
DOI: 10.1111/head.12335
|View full text |Cite
|
Sign up to set email alerts
|

Imploding and Exploding Migraine Headaches: Comparison of Methods to Diagnose Pain Directionality

Abstract: Background The study aims to compare methods of determining headache directionality (imploding, exploding, and/or ocular headaches) in women with migraine, investigate the concordance between physician assignment and patient self-assignment of pain directionality, and evaluate whether patients assigned their headaches to the same direction when queried using different methods. Directionality of migraine headache pain (imploding, exploding, or ocular) may reflect differences in the underlying pathogenesis of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…23 The role of peripheral sensitization in migraine headache is based on the perception of imploding headache that hurts outside the cranium, 18 the existence of a network of sensory fibers that bifurcate from the parent axons of intracranial meningeal nociceptors and reach extracranial tissues such as periosteum and pericranial muscles by crossing calvarial bones through the sutures, 20 the discovery of upregulated proinflammatory genes and down-regulated anti-inflammatory genes in the extracranial tissue of chronic migraine patients, 22 and the reduction of headache frequency by administration of Onabotulinum toxin A in the peripheral tissues outside the calvarium. 21,23 In line with these findings, the long-term results of occipital nerve decompression surgery for relief of chronic headache with or without features were reported. 24 Among seven patients with chronic refractory occipital headache, occipital nerve decompression surgery resulted in compete elimination of new daily persistent headache and posttraumatic headache, and partial elimination of chronic headache/migraine in two patients.…”
Section: Peripheral Sensitization As a Pathophysiology Of Migrainesupporting
confidence: 55%
See 2 more Smart Citations
“…23 The role of peripheral sensitization in migraine headache is based on the perception of imploding headache that hurts outside the cranium, 18 the existence of a network of sensory fibers that bifurcate from the parent axons of intracranial meningeal nociceptors and reach extracranial tissues such as periosteum and pericranial muscles by crossing calvarial bones through the sutures, 20 the discovery of upregulated proinflammatory genes and down-regulated anti-inflammatory genes in the extracranial tissue of chronic migraine patients, 22 and the reduction of headache frequency by administration of Onabotulinum toxin A in the peripheral tissues outside the calvarium. 21,23 In line with these findings, the long-term results of occipital nerve decompression surgery for relief of chronic headache with or without features were reported. 24 Among seven patients with chronic refractory occipital headache, occipital nerve decompression surgery resulted in compete elimination of new daily persistent headache and posttraumatic headache, and partial elimination of chronic headache/migraine in two patients.…”
Section: Peripheral Sensitization As a Pathophysiology Of Migrainesupporting
confidence: 55%
“…The author did not attempt GON decompression for chronic migraine, but rather in terms of referred facial pain due to GON entrapment. This case suggests that peripheral sensitization may be related to pathophysiology, [18][19][20][21][22][23][24] especially when the referred facial pain is accompanied by migraine without aura.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…There has been a novel distinction between migraine attacks in which the headache is perceived as exploding, as in a pressure buildup inside the head, and those in which the headache is perceived as imploding, like deformed, crushed or broken calvarial bones, with the pain often described as being inflicted from the outside (imploding headache) by a sharp knife or a more widely spread like a vise-like squeeze [8, 13]. This distinction gained mechanistic attention when it was demonstrated that extracranial administration of OnabotulinumtoxinA is effective in reducing the number of migraine days per month in patients who testified to having ‘imploding’, but not in those who testified to having ‘exploding’ headache (Figure 1) [8, 14].…”
Section: The Perception Of Imploding Headache and Its Relief By Extramentioning
confidence: 99%
“…Traditionally migraine has been considered as a consequence of a neurovascular disorder with involvement of the central nervous system, newly some data support the hypothesis of compression or irritation of peripheral sensory nerves within muscles, fascia, bone and vascular spaces of the head and neck [5][6][7][8][9][10][11][12]. The irritation of extracranial sensory nerves may appear spontaneously or may derive from several factors, such as traumatic and postoperative ones: these can cause an injury to the nerves or their surrounding tissue so as to create a trigger point for the migraine headache [1].…”
Section: Introductionmentioning
confidence: 99%